Agricultural Productivity, Green Energy Consumption, Governance Quality, and Environmental Degradation in BRICS Economies. Evidence from a PMG-ARDL Approach - Kilani, Hadda; Benamar, Mohamed (Journal of Environmental Management and Tourism; Vol 17 No 1 (2026): JEMT, Volume XVII, Issue 1(81), Spring 2026DO - 10.14505/jemt.v17.1(81).02, 2026)
This study examines the relationships between agricultural productivity, green energy consumption, governance quality, and environmental degradation in BRICS economies. The main objective is to assess whether improvements in agricultural performance intensify environmental pressure and to what extent green energy adoption and institutional quality can mitigate these adverse effects. The analysis is based on a balanced panel dataset covering the period 2002–2023 and employs the Pooled Mean Group Autoregressive Distributed Lag (PMG-ARDL). The empirical findings reveal that agricultural productivity significantly increases environmental degradation in the long run, highlighting the environmental costs associated with agricultural intensification in emerging economies. In contrast, green energy consumption and governance quality exhibit strong and consistent pollution-reducing effects, contributing to improved environmental sustainability. This study provides original empirical evidence by jointly integrating agricultural productivity, green energy, and governance quality within a unified dynamic framework, offering important insights for designing sustainable agricultural and energy policies in emerging economies.